(untitled) (Symposium on Natural and Applied Sciences, 2026)
This article analyzes the role of non-state education in the education system of Uzbekistan, as well as the reforms implemented in recent years and their outcomes. Furthermore, it reveals the impact of the development of non-state education on social progress and the intellectual profile of society.